Time Analysis on the Kuningan Eastern Ring Road - Prasetyo, Sigit Widiyatmo; Darmawan, Dicky; Firdaus, Dinda; Kusumastuti, Aryati Indah (Indonesian Journal of Advanced Research, 2025)
This analysis aims to identify delay factors and reduce the risk of delay in construction projects using the CPM method in the construction project of the East Ring Road Kuningan. The results of the study show that common factors that can have an impact on delays include the provision of materials, workforce readiness, and schedule adjustment to weather conditions. Therefore, supervision and control on critical routes must be carried out intensively to ensure that the project can be completed on time according to plan because delays in one activity alone will have a direct impact on the overall project completion.